Association of Fatty Liver Severity and Endothelial Function in Non-Alcoholic Fatty Liver Disease (NAFLD) Patients - Pashaura Singh Sandhu; Singh, Jasdeep; Ramesh Chander; Kaur, Alaipreet (Asian Journal of Medical Research, 2020)
Background: Non alcoholic fatty liver disease is fast attaining the status of being the most common disease throughout the world. The present study was conducted to evaluate the association of fatty liver severity and endothelial function in Non-Alcoholic Fatty Liver Disease (NAFLD) patients. Subjects and Methods: The study was conducted on 50 non-alcoholic fatty liver disease subjects (cases) and 50 healthy volunteers (controls). Biochemical tests such as serum bilirubin, total serum protein, serum albumin, serum globulin, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) and prothrombin index (PTI) were performed. Brachial artery diameter and its changes, post cuff-deflation were determined. Blood Flow mediated vasodilatation (FMD), was determined ultrasonographicaly. Results: The mean baseline brachial artery diameter in cases was 3.88 mm and in control was 3.77 mm. The difference found to be non- significant (p> 0.05). The mean post cuff deflation brachial artery diameter in cases was 4.03 mm and in control was 4.17 mm. The difference found to be significant (p< 0.05). The mean flow mediated vasodilatation in cases was 0.15 and in control was 0.40. The difference found to be highly significant (p< 0.05). Conclusion: Authors found that the mean FMD in brachial artery in patients with non-alcoholic fatty liver disease is below normal range. Reduced percent FMV was associated with NAFLD.